Effect of Optimized Tilt Angle of PV Modules on Solar Irradiance for Residential and Commercial Buildings in Different Cities of Pakistan: Simulation‐Based Study - Habib Ullah Manzoor; Sheikh Muhammad Aaqib; Tareq Manzoor; Fawad Azeem; Muhammad Waqas Ashraf; Sanaullah Manzoor (Energy Science & Engineering)
ABSTRACT The tilt angle of a solar PV panel is a critical factor in improving the efficiency of photovoltaic (PV) systems. While tracking systems can enhance performance, they are typically not cost‐effective for residential areas. Alternatively, setting an optimized fixed tilt angle or adjusting the tilt seasonally can mitigate power losses. This study evaluates optimal seasonal tilt angles and the corresponding solar radiation on PV panels for 10 major cities across Pakistan. A novel mathematical framework is proposed to calculate the optimal tilt angle using parameters such as alignment, azimuth, gradient, and temporal angles. Seasonal adjustments are shown to increase solar intensity from 0.4 KWh/m 2 to 0.6 KWh/m 2 during winter, significantly enhancing output power. For instance, an improvement of up to 5.61 mW/cm 2 in output power density was observed at the Quaid‐e‐Azam Solar Park using crystalline solar cells. These findings demonstrate the potential for substantial improvements in solar power production through seasonally optimized tilt angles, particularly during the shorter winter days.